A inversão do cotidiano: práticas sociais e rupturas na vida urbana contemporânea - Rogerio Proença Leite (Universidade do Estado do Rio de Janeiro, 2010)
This article focuses on key approaches from social theory to analyze routine everyday life in order to affirm that certain frequent breaks occurring in the interstices of public life do not place the notion of daily existence at jeopardy - although they challenge it; on the contrary, they guarantee certain dynamics that are necessary for the social practices that spawn challenge and change. With an emphasis on Michel de Certeau's Theory of Practices, the article discusses the practices that challenge the disciplinary spaces through either daily tactics or counter-uses, with a view towards understanding the dynamic processes of everyday life in contemporary urban culture.